Effect of ligand attachment on the C-I bond dissociation process on aluminum nanoclusters: a DFT investigation - Sengupta, Turbasu; Samanta, Bipasa; Pal, Sourav (Journal of Physical Chemistry C, 2017)
The influence of the ligand attachment on the activation process of carbon halogen bond on small sized aluminum nanoclusters are investigated using density functional theory. Attaching suitable ligand to metal clusters is among the widely popular techniques often used by experimentalists in order to stabilize metastable clusters. In depth theoretical investigations have shown that based on the jellium configuration of the cluster, attaching an electron withdrawing ligand can either make a cluster more reactive toward the C-I dissociation or may convert the cluster relatively inert. The alteration of the activation barriers and other associated parameters due to ligand attachment are included in this paper along with additional calculations and explanations. The study also shows that even the reaction parameters of specific magic clusters can be significantly altered via ligand attachment. The activation process of small molecules on metal clusters are of crucial importance for the development of material science and cluster chemistry. The present investigation will therefore be useful for better understanding of the properties of the ligated clusters as well as may also aid the experimentalists toward controlling the reactivity of a specific cluster as required.

Specificity of amino acid-aluminum cluster interaction and subsequent oxygen activation by the above complex - Samanta, Bipasa; Sengupta, Turbasu; Pal, Sourav (Journal of Physical Chemistry C, 2018)
Amino acid aluminum cluster complex has been shown to be a promising oxygen molecule activator and has the potential to dissociate O-O bond on the cluster surface. The study of the complex also reveals specificity of amino acid to aluminum cluster in the above complex, which can be used in the detection of amino acid. The results have been obtained by the density functional theory at the B3LYP/6-311++g(d,p) level of calculation.

Aluminum cluster for CO and O-2 adsorption - Samanta, Bipasa; Sengupta, Turbasu; Pal, Sourav (Journal of Molecular Modeling, 2019)
Low temperature oxidation of CO to CO2 is an important process for the environment. Similarly adsorption of CO from the releasing sources is also of major concern today. Whereas the potential of gold and silver clusters is well proven for thecatalysis of the above mentioned reaction, the potential of aluminum (Al) clusters remains unexplored. The present study proves that, similar to the transition metals, Al clusters can also be used for adsorption of gases. We first tested the potential of Al cluster as adsorbents for CO. The high binding energy (BE) values prove that Al clusters can be used for adsorbing both CO and O-2. Since oxygen binding is more facile, we adsorbed oxygen on Al and then checked the effect of this O-2 on the BE of CO. The results were obtained by DFT calculations at M062X/TZVP level of theory.
Keywords: Aluminum clusters; Charge decomposition analysis; CO adsorption; DFT; O-2 adsorption; Wiberg bond indices